Implementasi Blended Learning pada Masa Pandemi Covid-19 dalam Mengembangkan Karakter Kemandirian dan Tanggung Jawab Anak Usia Dini - Yulianti Sholihah; Faiz Karim Fatkhullah; Shinta Mutiara Puspita (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
The problem in this study is the Covid-19 pandemic which has an impact on the world of education, especially at Diana Safira Kindergarten, which results in having to adapt to government policies regarding the rules of learning activities that must continue to run and go hand in hand with the Covid-19 pandemic. The purpose of this study is to describe the implementation of blended leaning in developing the character of independence and responsibility of children aged 5-6 years at Diana Safira Kindergarten. This research method uses Descriptive method with Qualitative approach. Data collection techniques using interviews, observation and documentation techniques. The results of this study that the planning and learning process follow government policies related to learning during the Covid-19 pandemic. During the Covid-19 pandemic, the role of parents is very necessary for PAUD to act as educators, act as facilitators, act as supervisors and companions, act as motivators, act as examples of good figures. Learning constraints during the Covid-19 pandemic due to lack of attention and cooperation of parents to learn online and face-to-face is limited. The implementation of blended learning during the Covid-19 pandemic in improving the character of independence and responsibility of children can be realized well if there is cooperation between the school and parents